Gravity influence on the performance of micro direct methanol fuel cell. (December 2015) - Fu, Wenting; Yuan, Zhenyu; Zhang, Yufeng; Wang, Zi; Liu, Xiaowei
The influence of gravity on mass transport and micro direct methanol fuel cell performance is presented in this article. A multi-physics three-dimensional model calculated by COMSOL Multiphysics is established. The results show that gravity significantly affects the distribution of pressure and methanol concentration. To verify the simulation, a self-breathing transparent micro direct methanol fuel cell with horizontal orientation and vertical orientation is designed, fabricated and tested. The polarization curves of horizontal orientation exhibit the best performance with the power density of 25.57 mW cm −2 . Moreover, the cell placed with horizontal orientation exhibits faster CO2 emission velocity than that of the cell with vertical orientation.